(Economic Role of the Gulf Arab Ports and Their Impact on Relations with the Countries of Iraq (3rd millennium BC and until the middle of the millennium BC - Al Rahaily, Rawan Faisal Mohammed (Journal of Economic, Administrative and Legal Sciences, 2018)
It is based on studying the cultural role of the Gulf Arab economic ports in the period of time specified and the impact of the geography of the Arabian Gulf and its importance and the composition of the islands and the emergence of ports in it and the result of convergence between the Arabian Gulf and Iraq through continuous economic relations and mutual interests, And the names of the ancient Arabian Gulf to the ancient Iraqis, as well as the most important economic ports of the region (Delmon and Majan), The transit trade and the elements of economic activity, and the commercial goods that boosted the economy of the region and its emphasis on agriculture, industry and trade and the methods of dealing in ports and markets. explaining the manifestations of political life in the region and the interests of the kings of Iraq and their keenness to develop political and economic relations to ensure trade routes either through control (the intellectual influences), especially the religious life represented by the myths, as it related to trade relations, the most important findings of the research, followed by a list of sources and references Which has been referenced.